The Effects of Aging on Clinical Vestibular Evaluations - Maheu, Maxime; Houde, Marie-Soleil; Landry, Simon P.; Champoux, François (Frontiers in Neurology, 2015)
Balance disorders are common issues for aging populations due to the effects of normal aging on peripheral vestibular structures. These changes affect the results of vestibular function evaluations and make the interpretation of these results more difficult. The objective of this article is to review the current state of knowledge of clinically relevant vestibular measures. We will first focus on otolith function assessment methods cVEMP and oVEMP, then the caloric and vHIT methods for semi-circular canals assessment. cVEMP and oVEMP are useful methods, though research on the effects of age for some parameters are still inconclusive. vHIT results are largely independent of age as compared to caloric stimulation and should therefore be preferred for the evaluation of the semi-circular canals function.